Minoan plaster technology as evident from the ‘precinct’ structure at Koumasa, Crete: a microarchaeological study - Boness, Doron; Panagiotopoulos, Diamantis; Goren, Yuval (Journal of archaeological science reports, 2017)
Twelve plaster units and two sediment blocks from the ‘precinct’ structure at the Minoan site of Koumasa, Crete, were sampled for a microarchaeological study, with the aim of examining the technology of their production and pigment production and application techniques, employing micromorphology, pXRF and ESEM/EDS. The results demonstrate that plaster and pigment technologies at the site followed common procedures in contemporaneous regional centers, and in the Aegean and eastern Mediterranean cultural sphere. However, certain flexibility and local adaptations of these technologies are also apparent, varying with the plasters' structural function, availability of raw materials and local cultural conventions. In addition, the high utility in preparing thin sections on-site is demonstrated, allowing for the use of thin sections for further study by ESEM/EDS. This, together with the employment of portable equipment at the site allow for a thorough study of ancient archaeological materials and technologies.